High Frequency Measurements of Dielectric Behavior of Ceramic Materials Using free Space Method: Characterization and Validation of Dielectric Properties of Ceramic Materials in High Frequency Range (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The dielectric properties measurements of some dielectric materials, used in microwave and millimeter wave technology, are performed in F band (90-140 GHz) by using free space technique. A system, which consist a Performance Network Analyzer, two pyramidal horn antennas, a quasi-optical bench and an in house developed code TTDS are used in measurements. The measurement results are also verified by the simulation results obtained by CST-Microwave Studio